Field experiments in economics: Palgrave entry - John A. List; David Reiley (Institute for the Study of Labor (IZA), 2008)
Field experiments occupy a middle ground between laboratory experiments and naturally occurring field data. The idea is to perform a controlled experiment that captures important characteristics of the real world. Relative to traditional empirical economics, field experiments provide an advantage by creating exogenous variation in the variables of interest, allowing us to establish causality rather than mere correlation. Relative to a laboratory experiment, a field experiment gives up some of the control that a laboratory experimenter may have over her environment in exchange for increased realism.
Keywords: C72; 330; Field experiments; Feldforschung; Test